2016
DOI: 10.3390/en9020068
|View full text |Cite
|
Sign up to set email alerts
|

Device Performance Improvement of Double-Pass Wire Mesh Packed Solar Air Heaters under Recycling Operation Conditions

Abstract: Abstract:The improvement of device performance of a recycling solar air heater featuring a wire mesh packing was investigated experimentally and theoretically. The application of the wire mesh packing and recycle-effect concept to the present study were proposed aiming to strengthen the convective heat-transfer coefficient due to increased turbulence. Comparisons were made among different designs, including the single-pass, flat-plate double-pass and recycling double-pass wire mesh packed operations. The colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…4 It has also been observed that by raising recycle proportion (R) from 0 to 2, the thermal efficiency of a double-pass wire mesh-packed SAH improves. 5 Different designs of the absorber plate, such as roughened multi V-rib with gap roughness, 6 protrusions, 7 roughened with rib-grooved, 8 W-shaped ribs, 9 discrete V-down ribs, [10][11][12] multiple v-rib, 13 multigap and V-down rib combined with staggered ribs, 14 wavy finned, 15 U-shaped turbulators, 16 V-baffle vortex generators, 17 and V-corrugated plate in the double-pass configuration 18 have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…4 It has also been observed that by raising recycle proportion (R) from 0 to 2, the thermal efficiency of a double-pass wire mesh-packed SAH improves. 5 Different designs of the absorber plate, such as roughened multi V-rib with gap roughness, 6 protrusions, 7 roughened with rib-grooved, 8 W-shaped ribs, 9 discrete V-down ribs, [10][11][12] multiple v-rib, 13 multigap and V-down rib combined with staggered ribs, 14 wavy finned, 15 U-shaped turbulators, 16 V-baffle vortex generators, 17 and V-corrugated plate in the double-pass configuration 18 have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…its discovered that the warm proficiency of the bask-strong air cooling with introducing wire work impeccable was expanded and more prominent than without wire work spotless about 34.81%. Ho et al [2] evaluated the improvement in thermal efficiency of a reused solar air heater using metallic wire-mesh theoretically and experimentally. They compared different configurations in which a single-pass flat-plate, double-pass and recycling double-pass which has a wire mesh packing.…”
mentioning
confidence: 99%